Pengaruh Aglomerasi Industri Terhadap PDRB di Provinsi Jawa Timur - Natalya, Diventi; Rachmawati, Lucky (Jurnal Ekonomika : INDEPENDEN, 2024)
This study aims to determine the effect of Industrial Agglomeration on Gross Regional Domestic Product (GRDP) in East Java province. The type of research used in this research is a type of quantitative research using panel data regression models. In this study there are two variables, namely GRDP as variable Y and Industrial Agglomeration as variable X. The results showed that the probability value of the industrial agglomeration variable was 0.0761 which was greater than 0.01. This states that partially industrial agglomeration has a positive and insignificant effect on GRDP in East Java province. It is hoped that the government can manage the allocation of the industrial sector sothat it can be evenly distributed throughout East Java.